Leveraged buyout spreads : a focus on loan maturity - Jesus, João Pedro dos Santos Monteiro de (2018)
This thesis investigates the determinant factors concerning pricing of loans in LBOs, the term structure of these loans, and determinants of loans maturity, using a sample of 1,196 syndicated loan deals closed from 2000 to 2016. Our results suggest differences in spreads and pricing processes in market-based versus bank-based financial systems as well as in the U.S. versus W.E. EV/EBITDA proved to not have great impact in spreads. Furthermore, the convex relationship found in previous literature [Sorge and Gardanecz (2008), Marques et al. (2015) and Pinto et al. (2016)] could be flattened with the relationship between spread and maturity/EBITDA multiple, with just a slight slope (diverging through the different sub-samples). Results indicate number of tranches, firm size, rentability and deal location to impact maturity in LBOs loans.